The development of enrichment book of chemistry in our body based on augmented reality and its influence on chemistry literacy and scientific attitude of high school student - Basri, Muhammad Fikri M; Ikhsan, Jaslin (Pascasarjana Universitas Negeri Medan, 2024)
This research aims of this research is to obtain produce enrichment book of chemistry in our body based on augmented reality which can display the 3D shape of molecular shape and chemical bonds developed from macromolecular materials that are suitable for increasing student chemical literacy and scientific attitude. This development research uses a 4D model developed by Thiagarajan which consists of stages Define, Design, Development, and Disseminate. The trial was carried out on 1 limited test class and 2 wide test classes (1 experimental class and 1 control class) of XII Science students at Senior High School of Angkasa Adisutjipto. The results of the research show that: 1) Enrichment book of chemistry in our body based on augmented reality that have been developed have very decent quality by media and materials validators; 2) the practicality response are included in the